2017
DOI: 10.1186/s12954-017-0174-x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and design preferences of supervised injection services among people who inject drugs in a mid-sized Canadian City

Abstract: BackgroundSupervised injection services (SIS) have been shown to reduce the public- and individual-level harms associated with injection drug use. While SIS feasibility research has been conducted in large urban centres, little is known about the acceptability of these services among people who inject drugs (PWID) in mid-sized cities. We assessed the prevalence and correlates of willingness to use SIS as well as design and operational preferences among PWID in London, Canada.MethodsBetween March and April 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
4
16
0
Order By: Relevance
“…Resulting stigma and discrimination may lead to social isolation or individuals choosing not to disclose their drug use, therefore making it challenging for some PWID to seek care [36]. Despite feasibility study results from another mid-size Canadian setting that found contrasting evidence to past research that suggests smaller cities lack liberal perspectives toward harm reduction and injection drug use [24], it remains unclear how these concerns may relate to the implementation of SIS in a geographically outlying mid-size city servicing suburban, rural and remote communities.…”
Section: Introductionmentioning
confidence: 99%
“…Resulting stigma and discrimination may lead to social isolation or individuals choosing not to disclose their drug use, therefore making it challenging for some PWID to seek care [36]. Despite feasibility study results from another mid-size Canadian setting that found contrasting evidence to past research that suggests smaller cities lack liberal perspectives toward harm reduction and injection drug use [24], it remains unclear how these concerns may relate to the implementation of SIS in a geographically outlying mid-size city servicing suburban, rural and remote communities.…”
Section: Introductionmentioning
confidence: 99%
“…NSP expansion efforts should also pay particular attention to the needs of homeless or unstably housed PWID, who were more likely to share syringes in unadjusted analyses. In addition, supervised injection services, which provide sterile injecting equipment and medically trained staff to supervise injections, are currently being planned as part of the response to drug-related harms in London (Middlesex-London Health Unit 2017; Mitra et al 2017). In Vancouver, use of such services has been associated with reduced syringe sharing (Kerr et al 2005), as well as a host of other public health and order benefits (e.g., reductions in fatal overdose (Marshall et al 2011) and public injecting (Wood et al 2004)).…”
Section: Discussionmentioning
confidence: 99%
“…From a public health perspective, allowing peer assisted injection can reduce other risks, since recipients have higher rates of sharing syringes and other paraphernalia (20) and as such, permitting this activity within a supervised facility may provide structured opportunities to enhance the health and safety of people who use drugs. Mitra et al (21) reported that 32% of potential SCS clients want assisted injection as a standard, operational feature onsite.…”
Section: The Public Health Value Of Peer-assistmentioning
confidence: 99%